Ascorbic Acid (Vitamin C) as a Cosmeceutical to Increase Dermal Collagen for Skin Antiaging Purposes: Emerging Combination Therapies - Yong Chool Boo (MDPI AG, 2022)
Ascorbic acid (AA) is an essential nutrient and has great potential as a cosmeceutical that protects the health and beauty of the skin. AA is expected to attenuate photoaging and the natural aging of the skin by reducing oxidative stress caused by external and internal factors and by promoting collagen gene expression and maturation. In this review, the biochemical basis of AA associated with collagen metabolism and clinical evidence of AA in increasing dermal collagen and inhibiting skin aging were discussed. In addition, we reviewed emerging strategies that have been developed to overcome the shortcomings of AA as a cosmeceutical and achieve maximum efficacy. Because extracellular matrix proteins, such as collagen, have unique amino acid compositions, their production in cells is influenced by the availability of specific amino acids. For example, glycine residues occupy 1/3 of amino acid residues in collagen protein, and the supply of glycine can be a limiting factor for collagen synthesis. Experiments showed that glycinamide was the most effective among the various amino acids and amidated amino acids in stimulating collagen production in human dermal fibroblasts. Thus, it is possible to synergistically improve collagen synthesis by combining AA analogs and amino acid analogs that act at different stages of the collagen production process. This combination therapy would be useful for skin antiaging that requires enhanced collagen production.